A study evaluating knowledge of and attitude towards hepatitis B among pregnant women at a teaching hospital in Nellore, India. - Munivenkatappa, Swetha; Govindaraj, Srinivas M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hepatitis B infection is a common and preventable infection in India. Mother to child transmission is the most common method of infection in our country. Awareness regarding hepatitis B among pregnant women is important to take preventive measures like screening during pregnancy, vaccination of child. Studies evaluating knowledge, attitude and practice (KAP) towards hepatitis B among the pregnant women in our country are sparse. Methods: A cross sectional survey was conducted to evaluate KAP towards hepatitis B among pregnant women was conducted after handing over an information hand-out. Data was collected using a standard questionnaire with three sections: i) Demographic data ii) Knowledge questions iii) Attitude and Practice questions. Results: 42% of the 350 participants were aware about hepatitis B infection. The mean knowledge score was 6.33 (±2.86). Only 33.3% were aware that hepatitis B is transmitted by unprotected sex and 8.2% were knowledgeable of mother to child transmission. The mean attitude/practice score was 2.97 (±1.69). Only 30% would insist on safe equipment and blood/blood products. 84% would hesitate to have casual contact with hepatitis B infected persons. Most feared the stigma associated with hepatitis b infection than its health consequences. 70% would vaccinate their child to prevent hepatitis B infection. Women with greater knowledge about hepatitis B had better attitude/practice towards its prevention. Conclusions: Knowledge about HBV among pregnant women was poor and needs to be improved to prevent mother to child transmission. Educational programs need to be tailored for the target population for better uptake.